Histopathological Effects Of Extracts Of Two Indigenous Plants, Pongamia Pinnata (L.) Pierre And Clerodendrum Viscosum (Vent.) On The Cat Fish, Heteropneustes Fossilis (Bloch) - Nasiruddin, Munira; Azadi, Mohamad Ali; Nely, Mahmuda Sharmin (Journal of the Asiatic Society of Bangladesh, Science, 2013)
Piscicidal properties of part extracts (seed, leaf and bark) of two indigenous plants, Pongamia pinnata (L.) Pierre and Clerodendrum viscosum (Vent.) were studied on Heteropneustes fossilis (Bloch). A number of histopathological lesions was observed in the tissues of intestine, gill and liver of the fish which were treated with 50% ethyl alcohol extract of the two plant parts toxicants. The principal degenerative changes in the intestine were: disintegrated serosa, swollen and partially ruptured muscularis layer, vacuolated submucosa, damaged mucosa and distended and coalesced villi. The principal changes in the gills included vacuolated and disrupted epithelial cells and disorganized gill filaments, shrunken and oedamatous distensions in the primary lamellae, swollen, shortened and coalesced secondary lamellae and distorted and disintegrated gill arches. The changes in the liver included compactly or loosely arranged hepatic cells, reduced or swollen hepatic artery, disintegrated hepatic vein, blood coagulated portal vein, dilated and swollen central vein and dispersed sinusoids. The most toxic extract for P. pinnata was the leaf extract and for C. viscosum was the seed extract in three organs. Among the extracts of three plant parts (seed, leaf and bark) P. pinnata was found to be more toxic than C. viscosum. J. Asiat. Soc. Bangladesh, Sci. 39(1): 105-115, June 2013 DOI: http://dx.doi.org/10.3329/jasbs.v39i1.16039